Ligation of the left renal vein in epm1-wistar rats: functional and morphologic alterations in the kidneys, testes and suprarenal glands - Baptista-Silva, José Carlos Costa; Dolnikoff, Miriam Sterman; Moura, Luiz Antonio Ribeiro; Pestana, José Osmar Medina; Vieira, Jose Gilberto Henriques; Miranda Jr, Fausto; Schor, Nestor; Peres, Clovis de Araujo; Burihan, Emil (São Paulo Medical Journal, 1997)
OBJECTIVE: The ligation of the left renal vein (LLVR) in man is a contraversial procedure in view of the risks of lesion to the renal parenchyma. With the objective of studying the morphologic and functional alterations caused by these lesions, we conducted experimental research with rats. MATERIAL AND METHODS: 64 male adult EPM1-WISTAR rats were used, divided into 8 groups - 4 for LLRV and four for control. Each LLRV group and corresponding control group were sacrificed progressively on the 7th, 15th, 30th and 60th day after the initial surgery. RESULTS: We found morphofunctional alterations only in animals that underwent LLRV in the four periods of sacrifice.The proteinuria creatinine in serum, testosterone in serum and serum corticosterone in serum showed practically no alteration in relation to the normal values for rats. Statistically significant severe histological lesions were found in the kidneys and testes of the LLRV groups. Lesions in the suprarenal glands were also present in these groups, but no sufficient to demonstrate statistical significance CONCLUSION: Based on these results we can conclude that the ligation of the left renal vein is a procedure of high risk in these animals.